Recontextualization of Islamic Educational Thought within Fazlur Rahman's Intellectual Framework - Suparman, Suparman; Nasri, Ulyan; Zulkifli, Muh. (Jurnal Ilmiah Profesi Pendidikan, 2023)
Fazlur Rahman, a prominent Islamic thinker who advocated a contextual and relevant approach to contemporary developments. This study aims to examine and analyze the concept of recontextualization of Islamic educational thought within Fazlur Rahman's intellectual framework. The research method employed is document analysis, involving critical reading and evaluation of Fazlur Rahman's writings and relevant literature. The findings of this research emphasize a deeper understanding of the recontextualization approach to Islamic educational thought proposed by Fazlur Rahman, and how this thinking can significantly contribute to addressing the challenges of Islamic education in the modern context. The conclusion of this study provides a better understanding of the recontextualization of Islamic educational thought within Fazlur Rahman's intellectual framework, offering valuable insights for educators, social scientists, and practitioners of Islamic education in their efforts to develop relevant and meaningful Islamic education in the contemporary era.